Los programas de salud escolar y el rol del Trabajador social en la escuela Dr. Edison Calle loaiza de la ciudad de Loja - Abarca Muñoz, Joffre Alexander (2012)
The Education and the Health are two of the most important social conquests obtained by the Ecuadorian town. The indicators that are revealed in an and another sphere are samples truthful of the priority that is granted to the formation of the girls and children in the preservation, care of their health. This attention is not single responsibility of the sector of the Health, because this it is a social product and as such, it commits to the whole society. For what our investigation work carried out in the School Dr. Edison Loaiza Remains silent it reflects combined activities with the Area of Health Number 2 Daniel Álvarez Burneo and the Educational Community so that the students is beneficent of the Programs of School Health that executes the Ministry of Health it Publishes. In accordance with the results of the field work and contrasting with the current reality, a many problems is observed generated by the indifference of the directive of the educational facility; Which doesn't allow the access of the Medical Team so that the students is beneficent of the Programs of School Health. In this occasion the proposers of the present investigation work will meditate about the bad health that you/they have the students: In many occasions the bad health of the students do not allow to have an appropriate integral development that which affects in the teaching process - learning. On the other hand, an impediment for the non-applicability of the Programs of School Health is the nonfulfillment of the lists of the Educational Trident and of the Government and not Government Institutions because the society doesn't practice the civic inspectors to make respect the rights that attend him. It shows of we have it that the School Dr. Edison Loaiza Remains silent for the seven year-old lapse it has not existed any consent type and agreement with the external Institution so that the students is beneficent of the Programs of School Health; That which has impacted negatively in the integral health of the girls and the children. In general the responsible ones so that the girls and the children reach a good health we are all, that is to say to teach through the example, to cultivate being good models and second using means to build them first. It is also undeniable that when we all complete our lists, we exercise a positive influence in the education and the formation of the students; the progresses are more visible and more encouraging. Such, this is the reason. It feels pertinent and indispensable that the professional intervention in Social Work before the detected problem. "The indifference’s of the leadership of the School Dr. Edison Loaiza. Remains silent it does not allow the application of the Programs of School. The Health implemented by the National Government through the Ministry of Public Health, causing in the girls and the children illnesses that limit the appropriate integral development." The same rebounds in the emotional, social stability, and mainly in the academic yield of the students. Before, it is important the elaboration, planning and execution of a plan of social action guided to strengthen the active participation of those involved in it offers of improving the health and the quality of the girls' life and the children. For what the State will promote a culture for the health and the life, with emphasis in the alimentary education – nutritional. The girls and the children of the different educational institutions by means of the Programs of School Health, developing activities starting from the family, but without forgetting the individual and specific actions that correspond the girls and the children in an integral way. On the other hand, the integral attention to the girls and the children will be through the following ones you program sexual and reproductive health, mental health, nutrition, physical activity, mouth health, etc. This work constitutes a collective effort and serious study. The result of the experiences developed in the whole process and it fills a hole. The sense of integrating the diverse modalities of Promotion of the Health in the School Dr. Edison Loaiza Remains silent, making emphasis in the health like a right, with the participation of the Educational Trident to foment the health, as an integrated process of construction of their citizenship.